MICROBIOLOGICAL ASSESSMENT OF MUTTON INTENDED FOR EXPORT FROM ElKADARO EXPORT SlAUGHTER HOUSE, SUDAN - Mohammed Elhassan, Ibrahim; ElaminAbdelgadir, Atif; Eltayeb Ibrahim, Abedalaziz (Journal of Veterinary Medicine and Animal Production, 2022)
The study is planned to evaluate the hygienic quality of mutton intended for export from Elkadaro Slaughter House on basis of surface bacterial contamination. Seventy five samples (swabs) were collected during five visits, 15 samples in each visit (five samples for each: slaughter hall, slaughter house chiller and the refrigerated vehicle at Airport after unloading). The results of the bacterial counts revealed relatively high counts which(ranged between 1×103 - 6×106 CFU/ cm2), but without critical contamination levels according to the cut-off (critical) point for fresh meat (106 CFU/ cm2) and chilled meat (107 CFU/ cm2) .